Between smart technologies and Soviet guns: imaging the new heroic figure in postdigital warfare. Issue 2 (4th May 2019) - Ploeger, Daniël
ABSTRACT: In March 2017, I travelled to the frontline between the Ukrainian army and Pro-Russian separatist forces in the Donbass region, East Ukraine, as part of a research project into the return of twentieth century weapons in digital culture across Europe. While embedded in a patrol with soldiers of the Ukraine Volunteer Corps, an organization affiliated with the nationalist Right Sector movement, I ended up in a firefight on the edge of the no man's land. I documented how the soldiers alternatingly operated Soviet-era Kalashnikov assault rifles and contemporary consumer technologies, such as smartphones an action cameras. I will read the simultaneous performance of the soldiers with weapon and consumer technologies from different eras from the perspective of Russell Davies' concept of the post-digital, in relation to selfie practices and microcelebrity performance in networked culture. In this context, I will reflect on Alain Badiou's concept of the soldier as 'heroic figure'. In response to Badiou's claim that the traditional soldier is no longer an effective symbolic trope in a highly technologized culture, I will reflect on the – embodied and digitally networked – soldiers I accompanied as possible heroic figures of the post-digital.